Gluten-free diet does not influence the occurrence and the Th1/Th17-Th2 nature of immune-mediated diseases in patients with coeliac disease. Issue 7 (July 2016) - Imperatore, Nicola; Rispo, Antonio; Capone, Pietro; Donetto, Sara; De Palma, Giovanni Domenico; Gerbino, Nicolò; Rea, Matilde; Caporaso, Nicola; Tortora, Raffaella
Abstract: Introduction: Coeliac disease (CD) is the most common Th1-mediated enteropathy, frequently associated with other immune-mediated disorders (IMD). Aims: To evaluate: (1) the prevalence of IMD at the time of and after CD diagnosis; (2) a possible change in immune response to gluten free diet (GFD); (3) the potential role of GFD in reducing and/or preventing IMD in CD. Methods: Prospective study including all consecutive adult CD patients who underwent investigations for Th1-Th17/Th2-IMD at the time of CD diagnosis and after a 5-year follow-up period. Results: 1255 CD were enrolled. Of these, 257 patients (20.5%) showed IMD at the time of CD diagnosis, with 58.4% presenting a Th1/Th17-IMD. After a 5-year follow-up period, 682 patients (54.3%) showed new IMD despite GFD. Of these, 57.3% presented a Th1/Th17-IMD and 42.7% a Th2-IMD ( p  = 0.8). When compared the prevalence of each type of IMD before and after CD diagnosis, we did not identify any significant "switch" from Th1/Th17- to Th2-IMD or vice versa. The number of patients with Th1/Th17- and/or Th2-IMD increased during the GFD period (20.5% vs 54.3%; p  < 0.01; OR 1.9). Conclusions: The prevalence of IMD at the time of CD diagnosis is high and it seems to increase in the follow-up period despite GFD.